The Theory of Housing and Interest Rates - Kau, James B.; Keenan, Donald (Journal of Financial and Quantitative Analysis, 1980)
This paper studies the relationship between real interest rates and housing using a microeconomic approach. The primary impact of interest rates is on the demand side. The partial equilibrium, comparative static model of demand behavior presented is based on intertemporal preference maximization subject to a multiperiod income constraint. The model is always in terms of real prices and interest rates and operates in discrete time. Consumer preferences are represente by a smooth utility function which depends on two kinds of goods, housing and other nondurables. This study is couched in a neoclassical framework with all markets assumed perfect unless otherwise specified. With this approach the theory of housing and interest rates becomes part of standard consumer theory, rather than being based on inappropriate present value considerations.